Spatial and temporal variability of trace gas columns derived from WRF/Chem regional model output: Planning for geostationary observations of atmospheric composition. (October 2015) - Follette-Cook, Melanie B.; Pickering, Kenneth E.; Crawford, James H.; Duncan, Bryan N.; Loughner, Christopher P.; Diskin, Glenn S.; Fried, Alan; Weinheimer, Andrew J.
Abstract: We quantify both the spatial and temporal variability of column integrated O3, NO2, CO, SO2, and HCHO over the Baltimore/Washington, DC area using output from the Weather Research and Forecasting model with on-line chemistry (WRF/Chem) for the entire month of July 2011, coinciding with the first deployment of the NASA Earth Venture program mission Deriving Information on Surface conditions from Column and Vertically Resolved Observations Relevant to Air Quality (DISCOVER-AQ). Using structure function analyses, we find that the model reproduces the spatial variability observed during the campaign reasonably well, especially for O3 . The Tropospheric Emissions: Monitoring of Pollution (TEMPO) instrument will be the first NASA mission to make atmospheric composition observations from geostationary orbit and partially fulfills the goals of the Geostationary Coastal and Air Pollution Events (GEO-CAPE) mission. We relate the simulated variability to the precision requirements defined by the science traceability matrices of these space-borne missions. Results for O3 from 0 to 2 km altitude indicate that the TEMPO instrument would be able to observe O3 air quality events over the Mid-Atlantic area, even on days when the violations of the air quality standard are not widespread. The results further indicated that horizontal gradients in CO from 0 to 2 km would be observable over moderate distances (≥20 km). The spatial and temporal results for tropospheric column NO2 indicate that TEMPO would be able to observe not only the large urban plumes at times of peak production, but also the weaker gradients between rush hours. This suggests that the proposed spatial and temporal resolutions for these satellites as well as their prospective precision requirements are sufficient to answer the science questions they are tasked to address. Highlights: We quantify spatial and temporal variability of column integrated trace gases. We compare WRF/Chem trace gas variability with that observed during DISCOVER-AQ. We relate WRF/Chem variability to the precision requirements (PR) defined for TEMPO. The TEMPO instrument will resolve O3 air quality events over the US Mid-Atlantic. TEMPO resolution and PRs are sufficient to answer AQ-relevant science questions.